CHIKVPRO ‐ a protein sequence annotation database for chikungunya virus - Mishra, Akaash Kumar (Biomedical Informatics, 2010)
In the recent past, there has been a resurgence of interest in Chikungunya virus (CHIKV) attributed to massive outbreaks of Chikungunya fever in the South-East Asia Region. This has reflected in substantial increase in submission of CHIKV genome sequences to NCBI (National Center for Biotechnology Information) database. Hereby we submit a database “CHIKVPRO” containing structural and functional annotation of Chikungunya virus proteins (25 strains) submitted in the NCBI repository. The CHIKV genome encodes for 9 proteins:4 non-structural and 5 structural. The CHIKVPRO database aims to provide the virology community with a single accession authoritative resource for CHIKV proteome- with reference to physiochemical and molecular properties, proteolytic cleavage sites, hydrophobicity, transmembrane prediction, and classification into functional families using SVMProt and other Expasy tools. AVAILABILITY: The database is freely available at http://www.chikvpro.info/